Aggregation behaviors of gradient and diblock copoly(2-oxazoline) monolayers at the air-water interface. (27th October 2022) - Jeong, Jiwon; Ryu, Jungju; Jeong, Younhee; Kroneková, Zuzana; Kronek, Juraj; Sohn, Daewon
Abstract: This study reveals the different behavior of amphiphilic gradient and diblock copolymers based on aliphatic and aromatic 2-oxazolines. The copolymers were synthesized by the polymerization of hydrophilic 2-ethyl-2-oxazoline with hydrophobic 2-(4-octyloxyphenyl)-2-oxazoline. The aggregation behavior of gradient and diblock copolymers with different ratios between hydrophilic and hydrophobic units was explored. Surface pressure (Π)–surface area ( A ) isotherms were measured at the air-water interface. The gradient copolymers produced higher surface pressures and smaller limiting areas, while the diblock copolymers exhibit relatively flexible behaviors. Langmuir–Blodgett monolayers were transferred on the hydrophilic silicon wafer substrates at various surface pressure levels, and the nanostructure of the films was investigated by using atomic force microscopy and X-ray reflectivity measurements. It was observed that the morphologies of gradient and diblock copolymers were similar, indicating that the films form a uniform monolayer. The diblock copolymers produced relatively small changes in thickness upon the compression, compared to the changes in gradient copolymer monolayer films. The thickness of the gradient copolymers which have a high hydrophilic ratio at low surface pressure increases by increasing surface pressure and hydrophobic ratio. But the diblock copolymers do not change the thickness by increasing the surface pressure and hydrophobic ratio. The results indicate that the gradient copolymer monolayers have relatively rigid domains where hydrophilic and hydrophobic parts are smeared. On the other hand, the diblock copolymer has a flexible hydrophilic cushioning effect. This study provides insights into the development of novel materials based on hydrophilic-hydrophobic interactions. Graphical abstract: Image 1 Highlights: The different behavior of amphiphilic gradient and diblock copolymers based on aliphatic and aromatic 2-oxazolines. The aggregation behavior of gradient and diblock copolymers with different ratios between hydrophilic and hydrophobic units was explored. The gradient copolymer monolayers have relatively rigid domains where hydrophilic and hydrophobic parts are smeared. The diblock copolymer has a flexible hydrophilic cushioning effect.